2010
DOI: 10.1016/j.ijfoodmicro.2009.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Reducing oyster-associated bacteria levels using supercritical fluid CO2 as an agent of warm pasteurization

Abstract: An innovative approach to Post-Harvest Processing (PHP) of oysters is introduced focusing on the effects of supercritical carbon dioxide (scCO 2 ) on bacterial contaminants trapped in the digestive system of oysters. Oysters were exposed to scCO 2 under two conditions: (1) 100 bar and 37 °C for 30 minutes and (2) 172 bar and 60 °C for 60 minutes. Using FDA standard guidelines for food analysis, variations in the Aerobic Plate Count (APC) was assessed. It was established that exposing oysters to CO 2 at 100 bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…The temperature of DPCD treatment is low enough to avoid the thermal effects of traditional pasteurization to food products and retain their freshlike physical, nutritional, and sensory qualities (Damar & Balaban, 2006). Some research had shown that DPCD treatment had significant lethal effect on microorganisms in liquid and solid foods (Garcia-Gonzalez, Geeraerd, Elst, Van Ginneken, Van Impe and Devlieghere, 2009;Meujo, Kevin, Peng, Bowling, Liu and Hamann, 2010;Spilimbergo, Elvassore, & Bertucco, 2002;Zhang et al, 2006). Meanwhile, some research had also showed that DPCD treatment could inactivate pectinesterase, lipoxygenase, polyphenol oxidase (PPO) and peroxidase (POD) either in pure enzymatic solutions or in real food systems such as fruit juice (Balaban, Arreola, Marshall, Peplow, Wei and Cornell, 1991;Chen, Balaban, Wei, Marshall, & Hsu, 1992;Gui et al, 2007;Liu, Gao, Peng, Yang, Xu and Zhao, 2008;Liu, Gao, Xu, Hao, Liu and Wang, 2010;Tedjo, Eshtiaghi, & Knorr, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of DPCD treatment is low enough to avoid the thermal effects of traditional pasteurization to food products and retain their freshlike physical, nutritional, and sensory qualities (Damar & Balaban, 2006). Some research had shown that DPCD treatment had significant lethal effect on microorganisms in liquid and solid foods (Garcia-Gonzalez, Geeraerd, Elst, Van Ginneken, Van Impe and Devlieghere, 2009;Meujo, Kevin, Peng, Bowling, Liu and Hamann, 2010;Spilimbergo, Elvassore, & Bertucco, 2002;Zhang et al, 2006). Meanwhile, some research had also showed that DPCD treatment could inactivate pectinesterase, lipoxygenase, polyphenol oxidase (PPO) and peroxidase (POD) either in pure enzymatic solutions or in real food systems such as fruit juice (Balaban, Arreola, Marshall, Peplow, Wei and Cornell, 1991;Chen, Balaban, Wei, Marshall, & Hsu, 1992;Gui et al, 2007;Liu, Gao, Peng, Yang, Xu and Zhao, 2008;Liu, Gao, Xu, Hao, Liu and Wang, 2010;Tedjo, Eshtiaghi, & Knorr, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations with non-pathogenic E. coli ATCC25922 as a challenge microorganism have been conducted (Melo Silva et al, 2013;Meujo et al, 2010;Tamburini, Foladori, Ferrentino, Spilimbergo, & Jousson, 2014) and few specifically reported equal or higher resistance of the strain to SCCO 2 treatments in comparison to E. coli O157:H7 (Choi, Bae, Kim, Kim, & Rhee, 2009;Kim, Rhee, Kim, & Kim, 2007). Although the use of L. innocua FSL C2-008 has never been reported in the field of SCCO 2 inactivation technology, the non-pathogenic L. innocua is the Listeria species (SMC) following (I) supercritical carbon dioxide (SCCO 2 ) treatment at 9.9 MPa and 35 C for 30 min, (II) peracetic acid treatments (100 ppm) (PAA100) at atmospheric pressure, 35 C for 30 min, (III) combined treatment with supercritical carbon dioxide at 9.9 MPa and 35 C for 30 min and with 50 ppm peracetic acid (SCCO 2 /PAA50), (IV) combined treatment with supercritical carbon dioxide at 9.9 MPa and 35 C for 30 min and with 100 ppm peracetic acid (SCCO 2 /PAA100), (V) 30-min pre-conditioning using peracetic acid (100 ppm) at unpressurized conditions as well as combined treatment with supercritical carbon dioxide at 9.9 MPa and 35 C for 30 min and with peracetic acid at 100 ppm (SCCO 2 /PAA100PC), and subsequent storage at 25 C for up to 21 d. Means (n ¼ 3) sharing common lower-case and upper case letters are not significantly different (P !…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also obtained by Sirisee et al (1998), who tested the SC-CD 2 tolerance (35 to 50 °C and 100 to 310 bar) of Escherichia coli and S. aureus inoculated into ground beef and higher pressures and temperatures significantly decreased the D-values of both bacteria and no cells survived at 50 °C. Meujo et al (2010) studied the effect of the supercritical CD 2 in microbial inactivation of entire oysters, obtaining 2 and 3 logarithmic reductions in the aerobic microorganisms count, under the conditions 100 bar and 37 °C for 30 minutes and 172 bar and 60 °C for 60 minutes, respectively. These results indicate effect of temperature (pasteurization), not only of pressure.…”
Section: Methodsmentioning
confidence: 99%